Imaging, Surgical, and Pathology Findings of a Myxoid Aortic Sarcoma: When Distal Embolization Uncovers a Bigger Problem - Calcaterra, Domenico; Rosati, Carlo M.; Renfro, Leslie A.; Vardas, Panayotis N. (AORTA, 2018)
Aortic sarcomas are a very rare condition typically characterized by a deceiving presentation. Making a correct diagnosis is based on the application of an algorithm which allows to identify the primary disease site and to obtain a tissue diagnosis. Surgical aortic resection with adjuvant therapy offers the best palliation, particularly in cases of well-differentiated tumors with no evidence of diffuse metastatic spread.
Keywords: aortic sarcoma; distal embolization; imaging; surgical resection; adjuvant therapy